Magnetic nanomaterials for wireless thermal and mechanical neuromodulation - Signorelli, Lorenzo; Hescham, Sarah Anna; Pralle, Arnd; Gregurec, Danijela (iScience, 2022)
Magnetic fields are very attractive for non-invasive neuromodulation because they easily penetrate trough the skull and tissue. Cell specific neuromodulation requires the magnetic field energy to be converted by an actuator to a biologically relevant signal. Miniaturized actuators available today range from small, isotropic magnetic nanoparticles to larger, submicron anisotropic magnetic nanomaterials. Depending on the parameters of external magnetic fields and the properties of the nanoactuators, they create either a thermal or a mechanical stimulus. Ferromagnetic nanomaterials generate heat in response to high frequency alternating magnetic fields associated with dissipative losses. Anisotropic nanomaterials with large magnetic moments are capable of exerting forces at stationary or slowly varying magnetic fields. These tools allow exploiting thermosensitive or mechanosensitive neurons in circuit or cell specific tetherless neuromodulation schemes. This review will address assortment of available magnetic nanomaterial-based neuromodulation techniques that rely on application of external magnetic fields.
CRIS-Team Scopus Importer:2022-11-25
Keywords: Applied sciences; Nanomaterials; Neuroscience

Magnetoelectric nanodiscs enable wireless transgene-free neuromodulation - Kim, Ye Ji; Kent, Noah; Vargas Paniagua, Emmanuel; Driscoll, Nicolette; Tabet, Anthony; Koehler, Florian; Malkin, Elian; Frey, Ethan; Manthey, Marie; Sahasrabudhe, Atharva; Cannon, Taylor M.; Nagao, Keisuke; et al. (Nature Nanotechnology, 2024)
Deep brain stimulation with implanted electrodes has transformed neuroscience studies and treatment of neurological and psychiatric conditions. Discovering less invasive alternatives to deep brain stimulation could expand its clinical and research applications. Nanomaterial-mediated transduction of magnetic fields into electric potentials has been explored as a means for remote neuromodulation. Here we synthesize magnetoelectric nanodiscs (MENDs) with a core–double-shell Fe3O4–CoFe2O4–BaTiO3 architecture (250 nm diameter and 50 nm thickness) with efficient magnetoelectric coupling. We find robust responses to magnetic field stimulation in neurons decorated with MENDs at a density of 1 µg mm−2 despite individual-particle potentials below the neuronal excitation threshold. We propose a model for repetitive subthreshold depolarization that, combined with cable theory, supports our observations in vitro and informs magnetoelectric stimulation in vivo. Injected into the ventral tegmental area or the subthalamic nucleus of genetically intact mice at concentrations of 1 mg ml−1, MENDs enable remote control of reward or motor behaviours, respectively. These findings set the stage for mechanistic optimization of magnetoelectric neuromodulation towards applications in neuroscience research.
CRIS-Team Scopus Importer:2024-10-25

Microfabrication Technologies for Nanoinvasive and High-Resolution Magnetic Neuromodulation - Ge, Changhao; Masalehdan, Tahereh; Shojaei Baghini, Mahdieh; Duran Toro, Vicente; Signorelli, Lorenzo; Thomson, Hannah; Gregurec, Danijela; Heidari, Hadi (Advanced Science, 2024)
The increasing demand for precise neuromodulation necessitates advancements in techniques to achieve higher spatial resolution. Magnetic stimulation, offering low signal attenuation and minimal tissue damage, plays a significant role in neuromodulation. Conventional transcranial magnetic stimulation (TMS), though noninvasive, lacks the spatial resolution and neuron selectivity required for spatially precise neuromodulation. To address these limitations, the next generation of magnetic neurostimulation technologies aims to achieve submillimeter-resolution and selective neuromodulation with high temporal resolution. Invasive and nanoinvasive magnetic neurostimulation are two next-generation approaches: invasive methods use implantable microcoils, while nanoinvasive methods use magnetic nanoparticles (MNPs) to achieve high spatial and temporal resolution of magnetic neuromodulation. This review will introduce the working principles, technical details, coil designs, and potential future developments of these approaches from an engineering perspective. Furthermore, the review will discuss state-of-the-art microfabrication in depth due to its irreplaceable role in realizing next-generation magnetic neuromodulation. In addition to reviewing magnetic neuromodulation, this review will cover through-silicon vias (TSV), surface micromachining, photolithography, direct writing, and other fabrication technologies, supported by case studies, providing a framework for the integration of magnetic neuromodulation and microelectronics technologies.
CRIS-Team Scopus Importer:2024-11-01
Keywords: magnetic stimulation; microfabrication; nanoinvasive; neuromodulation; neurophysiology